Fabrication of vertical gallium oxide PN diodes using homoepitaxial growth by MOCVD and ion implantation technology - Chih-Yang Huang; Xin-Ying Tsai; Fu-Gow Tarntair; Anoop Kumar Singh; Shao-Hui Hsu; Dong-Sing Wuu; Kenneth Järrendahl; Ching-Lien Hsiao; Ray-Hua Horng (Materials Today Advances)
The exceptional properties of wide-bandgap semiconductor β-Ga2O3 position it as a leading candidate for next-generation high-power and high-frequency electronic devices. In this work, we successfully fabricated high-performance vertical p-n junction diodes using homoepitaxial β-Ga2O3 grown on Sn-doped β-Ga2O3 substrates with a (010) orientation. A 600 nm thick undoped β-Ga2O3 epitaxial layer was grown by metalorganic chemical vapor deposition at 875 °C. Phosphorus ions were implanted at energies of 40–200 keV and doses ranging from 1 × 1013 to 1.6 × 1014 ions/cm2 to achieve p-type doping. The rapid thermal annealing at 1100 °C for 10 s activated the dopants, enabling p-type conductivity. Ni/Au and Ti/Al/Ni/Au ohmic contacts were deposited on the p-type β-Ga2O3 epitaxial layer and n-type substrate, respectively, to form vertical p-n junctions. The fabricated diodes demonstrated a forward voltage of 1 V (@ 10 A/cm2), a specific on-resistance of 1.271 mΩ cm2, and an impressive on/off current ratio of 1.52 × 107, with an ideality factor of 1.477. The diodes showed excellent stability and robustness in temperature-dependent and pulse current density-voltage measurements This work represents a significant advance in p-type β-Ga2O3 technology, demonstrating its viability for future power electronics and semiconductor devices.